2022
DOI: 10.1186/s40104-022-00693-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-199-5p regulates spermiogenesis at the posttranscriptional level via targeting Tekt1 in allotriploid crucian carp

Abstract: Background Sperm abnormalities are one of the primary factors leading to male sterility, but their pathogenesis is still unclear. Although miRNAs are suggested to exert important roles in the regulation of spermatogenesis at both transcriptional and posttranscriptional levels, little is currently known regarding the regulation of sperm flagella assembly by microRNAs (miRNAs). The role of miRNAs in the development of sperm abnormalities in sterile triploid fish has not been studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Specifically, miR‐199, miR‐449a and miR‐125 were significantly decreased in cauda sperm (by microarray analysis). Previous studies have demonstrated that miR‐199 is important for regulating spermiogenesis by binding to the 3’‐UTR of one of its target gene, Tekt1 47 . Tekt1 has been demonstrated to influence the production and maturation of sperm 47,48 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, miR‐199, miR‐449a and miR‐125 were significantly decreased in cauda sperm (by microarray analysis). Previous studies have demonstrated that miR‐199 is important for regulating spermiogenesis by binding to the 3’‐UTR of one of its target gene, Tekt1 47 . Tekt1 has been demonstrated to influence the production and maturation of sperm 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…47 Tekt1 has been demonstrated to influence the production and maturation of sperm. 47,48 Other studies have demonstrated that reduced miR-199 levels in IVF blastocysts decreases their viability and developmental potential. 49 miR-449 has been demonstrated to be significantly reduced in sperm of mice exposed to chronic stress and these changes persist to the early embryo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of ultrastructure also showed that the vestibule of adhesive eggs was recessed and wider than that of semi-buoyant eggs, which appears adaptive in adhesive eggs in facilitating sperm entry to attached eggs, in contrast with semi-buoyant eggs in which mixing of eggs and sperm during mating likely gives greater assurance of fertilization. However, the guidance mechanisms for sperm entry during fertilization in fishes remains relatively poorly understood [ 45 , 46 ], and the adaptive significance, if any, of the contrasting forms of vestibule between adhesive and semi-buoyant eggs of C. alburnus remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol can inhibit the proliferation and increases apoptosis in cancer cells by triggering apoptosis, cell cycle and downregulation of signaling pathways [10,[12][13][14] . Micro Ribonucleic Acid (RNA), as a small non-coding RNA, can regulate the RNA expression [15][16][17] . Previous study shows that microRNA (miR)-199 was low expressed in many cancers such as liver cancer, lung cancer etc.…”
mentioning
confidence: 99%